Mercury Pollution in Minamata - Yokoyama, Hisashi (Cham Springer Nature, 2018)
Methylmercury poisoning; Minamata disease; Methylmercury emission; Methylmercury intoxication; Pollution-related disease; Neurological syndrome; Chemical factory pollution; Chisso Corporation
English
Keywords: Environmental economics; Methylmercury poisoning; Minamata disease; Methylmercury emission; Methylmercury intoxication; Pollution-related disease; Neurological syndrome; Chemical factory pollution; Chisso Corporation